MicroRNA‐184 is induced by store‐operated calcium entry and regulates early keratinocyte differentiation. Issue 10 (27th January 2020) - Richardson, Adam; Powell, Andrew K.; Sexton, Darren W.; Parsons, Jason L.; Reynolds, Nick J.; Ross, Kehinde
Abstract: Extracellular calcium (Ca 2+ ) and store‐operated Ca 2+ entry (SOCE) govern homoeostasis in the mammalian epidermis. Multiple microRNAs (miRNA) also regulate epidermal differentiation, and raised external Ca 2+ modulates the expression of several such miRNAs in keratinocytes. However, little is known about the regulation of miR‐184 in keratinocytes or the roles of miR‐184 in keratinocyte differentiation. Here we report that exogenous Ca 2+ stimulates miR‐184 expression in primary epidermal keratinocytes and that this occurs in a SOCE‐dependent manner. Levels of miR‐184 were raised by about 30‐fold after exposure to 1.5 mM Ca 2+ for 5 days. In contrast, neither phorbol ester nor 1, 25‐dihydroxyvitamin D3 had any effect on miR‐184 levels. Pharmacologic and genetic inhibitors of SOCE abrogated Ca 2+ ‐dependent miR‐184 induction by 70% or more. Ectopic miR‐184 inhibited keratinocyte proliferation and led to a fourfold increase in the expression of involucrin, a marker of early keratinocyte differentiation. Exogenous miR‐184 also triggered a threefold rise in levels of cyclin E and doubled the levels of γH2AX, a marker of DNA double‐strand breaks. The p21 cyclin‐dependent kinase inhibitor, which supports keratinocyte growth arrest, was also induced by miR‐184. Together our findings point to an SOCE:miR‐184 pathway that targets a cyclin E/DNA damage regulatory node to facilitate keratinocyte differentiation. Abstract : Elevation of extracellular calcium evoked miR‐184 in primary human keratinocytes. In turn, exogenous miR‐184 induced growth arrest and differentiation of keratinocytes.